Comparison of High CPAP versus NIPPV in Preterm Neonates: A Retrospective Cohort Study - Ahmad, Hussain Alsaid; Deekonda, Veena; Patel, Waseemoddin; Thabane, Lehana; Shah, Prakesh S.; Mukerji, Amit (American Journal of Perinatology, 2021)
Objective The aim of this study was to compare outcomes following receipt of high continuous positive airway pressure (CPAP) versus nasal intermittent positive pressure ventilation (NIPPV) in extremely preterm neonates.Study Design We retrospectively compared outcomes of preterm neonates (22–28 weeks' gestation) following their first episode of either high CPAP (≥ 9 cm H2O) or NIPPV. Primary outcome was failure of high CPAP or NIPPV within 7 days, as determined by either need for intubation or use of an alternate noninvasive mode.Results During the 3-year study period, 53 infants received high CPAP, while 119 patients received NIPPV. There were no differences in the primary outcome (adjusted odds ratio 1.21; 95% confidence interval 0.49–3.01). The use of alternate mode of noninvasive support was higher with the use of high CPAP but no other outcome differences were noted.Conclusion Based on this cohort, there was no difference in incidence of failure between high CPAP and NIPPV, although infants receiving high CPAP were more likely to require an alternate mode of noninvasive support.Key Points
Keywords: noninvasive respiratory support; continuous positive airway pressure; noninvasive positive pressure ventilation; distending pressure; invasive mechanical ventilation